Evaluation of Adnexal Masses with Gray Scale Ultrasonography and Color Doppler Flow Imaging in the First Trimester of Pregnancy - Midrarullah Khan; Muhammad Zubair (Journal La Multiapp, 2020)
Sonography is common use in early pregnancy has led to the exposure of incidental adnexal masses more often. Assessment of grayscale and color Doppler sonography outcomes is as precise when based on static images. To determine the evaluation of adnexal masses with grayscale ultrasonography and color Doppler flow imaging in first trimester of pregnancy. This Cross Sectional study was conducted at the Department of Radiology, Jinnah Hospital, Lahore, Pakistan. The study was conducted from July to Dec 2019. The patients were selected by nonprobability convenience sampling. All pregnant patients were undergoing abdominal ultrasonography to detect the adnexal masses. The data was collected by the questionnaire. Overall 68 individuals involved in this study out of which 29(96.7%) are benign diseases on the left side of patients and malignant are only 1(3.3%). Patients having benign diseases of right-sided are 33(86.8%) and malignant are 5(13.2%). Benign diseases are 62(91.2%) out of which 43 patients had cystic, 15 are mixed and 4 are solid components. Malignant diseases are found only 6 patients out of which 3 are mixed and 3 are solid components. Majority of the adnexal masses identified in pregnancy is benign and will resolve suddenly. Doppler sonography has severe limitations in the differentiation of benign from malignant adnexal disease on the basis of low-impedance flow.